2007
DOI: 10.1677/joe-07-0050
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and neonatal nicotine exposure and postnatal glucose homeostasis: identifying critical windows of exposure

Abstract: Fetal and lactational exposure to nicotine at concentrations comparable with those in women who smoke causes impaired glucose tolerance in male offspring in postnatal life. It remains unknown whether there are critical windows of susceptibility to nicotine exposure. Female nulliparous Wistar rats were given saline vehicle or nicotine bitartrate (1 mg/kg per day) prior to pregnancy, which was then: A) discontinued during pregnancy and lactation; B) continued until parturition; C) continued until weaning; and D)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 43 publications
2
74
0
3
Order By: Relevance
“…Some studies have shown that fetal and postnatal NIC exposure causes impaired glucose tolerance in neonatal offspring (Somm et al 2008). According to Bruin et al (2007), NIC exposure from conception until lactation results in permanent b-cell depletion and subsequent impaired glucose tolerance. Therefore, the development of diabetes requires that NIC exposure occurs in both gestation and lactation periods.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that fetal and postnatal NIC exposure causes impaired glucose tolerance in neonatal offspring (Somm et al 2008). According to Bruin et al (2007), NIC exposure from conception until lactation results in permanent b-cell depletion and subsequent impaired glucose tolerance. Therefore, the development of diabetes requires that NIC exposure occurs in both gestation and lactation periods.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, it has been demonstrated that adult offspring from mothers who were exposed to nicotine during gestation and/or lactation become obese and have other metabolic disorders such as cardiovascular disorders, permanent b-cell loss, and insulin resistance (Bruin et al 2007, Somm et al 2009). Therefore, it seems that nicotine has the potential to act as an obesogenic factor in the offspring.…”
Section: Introductionmentioning
confidence: 99%
“…This was associated with some alterations in lipid profile of mothers and pups, such as higher high-density lipoprotein cholesterol (HDL-C). At weaning, offspring whose mothers were exposed to nicotine had type 2 diabetes (Bruin et al 2007) and increased adipose tissue weight (Soom et al 2008). When maternal nicotine exposure occurred only during lactation, the 15-day-old pups showed higher adiposity, hyperleptinemia, hypothyroidism, hypercorticosteronemia, and higher adrenal catecholamine content (Oliveira et al 2009.…”
Section: Introductionmentioning
confidence: 99%